Comparative analysis of measurement systems and methods for force and velocity determinations in loaded and unloaded vertical jumps - Silva-Pereyra, V.; Biancardi, C. M.; Fábrica, G. (Sports Biomechanics, 2025)
Vertical force and velocity are key elements for evaluating jump performance. This study investigated the measurement agreement of force and velocity computed from kinetics, using a force platform, and from kinematics, using a motion capture system, during unloaded and loaded (+20% of body weight) vertical jumps. Synchronized kinetics and kinematics recordings were taken from 23 young basketball players while performing countermovement jumps (CMJ) and squat jumps (SJ). Five measurement of force and nine of velocity were analysed to evaluate the impact of different approaches on results interpretation. Results were compared within groups, intra class correlation and Bland-Altman analyses. Our result showed that loaded conditions did not affect the force estimation through double differentiation of kinematics data, however in SJ a systematic error appeared. Motion capture system and force platform disagreements on different velocity computations were detected, which increased in loaded conditions. Also, we observed a low agreement between a theorical approach of velocity estimation and force platform. Our findings indicate a disparity in measurement agreement of vertical force and velocity across alternative computation techniques and conditions (loads and vertical jump type), and therefore care must be taken while choosing a methodology for evaluating these important variables.